Upaya Peningkatan Kemampuan Spritual Quotient Melalui Model Pembelajaran Habit Forming (Pembiasaan) pada pelajaran Akidah Akhlak di Kelas VIII MTS Nurul Iman Telaga Jernih - Saparia; Ahmad Fuadi; Muamar Al Qadri (Tut Wuri Handayani : Jurnal Keguruan dan Ilmu Pendidikan, 2022)
The inhibiting factor in increasing students' Spiritual Quotient abilities is that the implementation of learning during the COVID-19 pandemic has not yet fully taken place face-to-face. Instead, learning and teaching activities are limited to the implementation of online or online learning programs. So that the teacher of the Akidah Akhlak study area cannot apply the Habit Forming model by getting students used to applying the material being studied. This type of research was conducted in the form of Classroom Action Research (CAR). According to the type of research chosen, namely classroom action research, this research uses an action research model in the form of a spiral and one cycle to the next cycle. The results of the research in this study that the increase in students' Spiritual Quotient abilities in the pre-cycle to the third cycle. Based on the data of students' completeness scores in increasing the Spiritual Quotient ability in the Akidah Akhlak subject in the pre-cycle to cycle III, this is because in the second cycle the student's mastery value only reaches 77.5%, so based on the results of the coordination of researchers with teachers in the field of study of Akidah Akhlak, the application of the model Habit Forming in the field of study of Akidah Akhlak is continued until cycle III.